Wybrane aspekty rekreacyjnej funkcji lasu w opinii użytkowników - Gołos, Piotr (Leśne Prace Badawcze, 2013)
The results of a survey conducted in several Promotional Forest Complexes (PFC) in the Śląskie and Podlaskie regions, as well as the urban forests in Łodź and Warsaw, indicate that visitor preferences vary among forest sites. Those forests where visitors prefer to rest should be located in forests designated for recreation, and include elements of recreational infrastructure. Depending on characteristics of the forest in question (seaside, lakeside, or mountains), respondents preferred forest located near to the water’s edge, whereas in mountainous areas they selected open places (roads and openings). Urban residents more commonly chose sites deep within the forest, while hikers selected forest edges. The desired recreational infrastructure, included garbage cans and hiking trails as the most important elements among city dwellers, while hikers pointed to rest areas and information boards. The respondents consistently agreed on the type of recreational activities conducted in forests as well as on type of elements which determine the attractiveness of forests for rest and recreation. Independently of site characteristics and the research location, the most common activities for respondents were hiking and riding bicycle; and attractive elements were silence and calm as well as cleanliness of the forests. The Contingent Valuation Method (CVM) was used to evaluate respondents’ Willingness to Pay (WTP) for intensification of selected public forest functions and forest management, including recreational functions. The number of respondents who declared a hypothetical monetary amount or WTP>0 depended on the place where research was conducted (forest or respondent’s home); forest area covered by financing (forests in general or local forests where respondents reside); the type of question used to obtain the information on WTP; as well as the scope of financing (all public forest functions or just a recreational function). The average WTP declared per household per year varied from 41 PLN in 2002 to 150 PLN in 2006 for selected forest areas. The average overall state statistics for WTP was 52 PLN (non-timber forest functions in municipality) and 41 PLN (recreational management of forests in municipality). The respondents also underlined that the goods and services provided should be co-financed from both state and local budgets, and that such financing should go directly to the organizations conducting forest management.